The Contribution of Basic Psychological Need Satisfaction to Psychological Well-Being via Autonomous Motivation Among Older Adults: A Cross-Cultural Study in China and France - Tang, Minmin; Wang, Dahua; Guerrien, Alain (Frontiers in Psychology, 2021)
According to Self-Determination Theory (SDT), the satisfaction of the universal needs for autonomy, competence and relatedness is important in order to enhance autonomous motivation, which in turn promotes psychological well-being (PWB), regardless of age or culture. In contrast, some cross-cultural perspectives challenge SDT’s universalistic viewpoint, especially SDT’s view that autonomy yields universal positive effects across Western and Eastern societies. To test these theoretical frameworks across cultures, with special focus on the field of aging, this study examined the contribution of satisfying basic psychological needs to elderly people’s PWB from Eastern and Western cultures (China and France). Elderly retired people living at home (NChina = 510, Mage = 68.49 years; NFrance = 170, Mage = 71.19 years) were invited to complete surveys assessing these variables and providing demographic information. Consistent with the hypothesis of SDT, results from Structural Equation Modeling indicated that needs satisfaction facilitates autonomous motivation, which in turn promotes PWB in both elderly Chinese and French. Moreover, the finding from subsequent moderation analysis confirmed the moderating effect of culture in the relationship between competence satisfaction and PWB, with the contribution of competence satisfaction on PWB being stronger among elderly Chinese than elderly French (p < .05). Our findings suggest that, the broad applicability of SDT notwithstanding, attending to cultural differences in elderly care remains important.